Multiple Solutions for Nonlinear Dirichlet Problems with Concave Terms - Gasiński, Leszek; Papageorgiou, Nikolaos S. (Mathematica Scandinavica, 2013)
We consider a nonlinear parametric Dirichlet problem with parameter $λ>0$, driven by the $p$-Laplacian and with a concave term $λ|u|^{q-2}u$, $1